THE COMBINED ANTIVIRAL THERAPY AT PREGNANT WOMEN WITH VERIFIED DIAGNOSIS OF GENITAL HERPETIC INFECTIONS - Grishchenko, O.V.; Lakhno, I.V.; Lisitsina, N.V.; Pak, S.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The data of the combined antiviral therapy application for the treatment of genital herpes at pregnant women are presented. Totally 52 pregnant women with the diagnosed herpes of 2 types were investigated. 26 of them received Geviran in a complex with Immunoglobulin and Egistol (І group), and 26 – only Geviran (ІI group). It was shown  that the combined therapy of genital herpes (Geviran with Immunoglobulin and Engistol) application was more effective than antiviral monotherapy. The proposed method of treatment had expelled recurrent episodes of infection, intrauterine fetal infections and decreased abdominal delievery rate.